Strategi Pemasaran 4P Untuk Meningkatkan Daya Saing Pada Lapak Labu Pak Roni Di Pasar Ngronggo - Afandi, Misbaqul; Sumelvia Dewi, Anita; Hendratmoko, Suseno (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
The purpose of this study is to examine how the 4P strategy (Product, Price, Place, and Promotion) can enhance competitiveness at Lapak Labu Pak Roni. This research employed a qualitative method with two key informants, namely the owner and an employee. Data analysis was conducted using the Miles and Huberman model. The findings indicate that the implementation of the 4P marketing strategy (Product, Price, Place, and Promotion) at Lapak Labu Pak Roni has proven effective in maintaining business sustainability, increasing customer loyalty, and strengthening competitiveness in Ngronggo Market. The implication of this research shows that the 4P strategy is not only relevant for large businesses, but can also be a practical reference for traditional UMKM in improving competitiveness through product innovation and social media utilization.